Old Czech legends as an inspiration for pop music - Zemanová, Zuzana (Bohemica Olomucensia, 2012)
The aim of the paper is to show possibilities and examples of using old Czech legends as a kind of inspiration in pop music during the 20th century. It is focused especially on two records, which were released surprisingly in the same time (1975-1976), but completely independently on each other: Meč a přeslice by famous musicians Hana and Petr Ulrych with lyrics by Ladislav Kopecký and Staré pověsti české prepared by lyricist Jan Krůta and several composers, singers and groups like Václav Neckář or Modrý efekt. In spite of the same source of inspiration authors of these LPs approached to the material of legends differently. Kopecký tried to paraphrase the original stories, while Krůta wanted to modernize and update them for contemporary young people. Unfortunately, the both attempts were rather unsuccessful. After that the matter of old legends disappeared from pop music for long time, but came back in 1990s.